EVALUASI DIRI BERBASIS KOMBINASI TRADITIONAL PAPER-BASED DAN ELECTRONIC PORTFOLIO UNTUK MENINGKATKAN KEMAMPUAN MENULIS MAHASISWA - Ni Luh Putu Eka Sulistia Dewi (Universitas Pendidikan Ganesha, 2010)
The objective of this action-based research is to improve the students’ ability in writing narrativeand descriptive paragraphs by implementing self-evaluation in Traditional Paper-based Instructioncombined with the Electronic Portfolio. The research was conducted based on the prior observation,interview and pre-test conducted in the second semester (2D) of English Education Department,Language and Art Faculty of Undiksha in the academic year of 2006/2007. This study involved29 subjects who has problem in writing the paragraphs. At first, the students were really dependingon the lecturer, had less self-confidence and view the work subjectively. However, as they weregiven the treatment, their self-confidence was getting improved (independence). Moreover, theylearned how to take a risk, open, honest and judge the work objectively. More or less, it influencestheir achievement in writing the paragraphs. It can be seen from the improvement of the averagescore which is 25,67 (fair) in the pre-test, 32.17 (good) during the post-test 1 and 36.69 (very good)in post-test 2. The students’ ability in writing descriptive paragraph was better than narrative onebecause they learnt from their experience in narrative. The improvement of the students’ ability inthese two paragraphs also influenced their final score that was B.Kata Kunci: self-evaluation, traditional paper-based, electronic portfolio, writing